2017
DOI: 10.1016/j.cmi.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of matrix metalloproteinases in chronic Q fever

Abstract: Coxiella burnetii-induced MMP production may contribute to the development of chronic Q fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The transcriptome data show that Cm infection in OE-WT cells substantially up regulates these ECM genes, and thereby can trigger or disrupt cellular processes that are essential for processes including cellular growth, wound healing, and fibrosis, but are highly suggestive that Chlamydia infection can also have impact on processes such as cell migration, gene expression, and cellular differentiation in macrophages and other hematopoietically-derived cells [73,74]. Our findings support the investigations of others who have implicated several members of this subset of ECM proteins in various disorders associated with genital tract Chlamydia infections such as oviduct fibrosis and scarring, uterus and oviduct distention, and tubal damage caused by ectopic pregnancy [7580]. Because the transcriptome data show that TLR3-deficiency causes dysregulation in the gene expression levels of most of the ECM proteins identified by IPA, these data provides insight into a possible mechanism that expounds our recent report demonstrating thatTLR3 deficient mice suffer more severe genital tract pathology than wild-type mice during Cm infection [59].…”
Section: Discussionsupporting
confidence: 86%
“…The transcriptome data show that Cm infection in OE-WT cells substantially up regulates these ECM genes, and thereby can trigger or disrupt cellular processes that are essential for processes including cellular growth, wound healing, and fibrosis, but are highly suggestive that Chlamydia infection can also have impact on processes such as cell migration, gene expression, and cellular differentiation in macrophages and other hematopoietically-derived cells [73,74]. Our findings support the investigations of others who have implicated several members of this subset of ECM proteins in various disorders associated with genital tract Chlamydia infections such as oviduct fibrosis and scarring, uterus and oviduct distention, and tubal damage caused by ectopic pregnancy [7580]. Because the transcriptome data show that TLR3-deficiency causes dysregulation in the gene expression levels of most of the ECM proteins identified by IPA, these data provides insight into a possible mechanism that expounds our recent report demonstrating thatTLR3 deficient mice suffer more severe genital tract pathology than wild-type mice during Cm infection [59].…”
Section: Discussionsupporting
confidence: 86%
“…The transcriptome data show that Cm infection in OE-WT cells substantially up regulates these ECM genes, and thereby can trigger or disrupt cellular processes that are essential for processes including cellular growth, wound healing, and fibrosis, but are highly suggestive that Chlamydia infection can also have impact on processes such as cell migration, gene expression, and cellular differentiation in macrophages and other hematopoietically-derived cells [73,74]. Our findings support the investigations of others who have implicated several members of this subset of ECM proteins in various disorders associated with genital tract Chlamydia infections such as oviduct fibrosis and scarring, uterus and oviduct distention, and tubal damage caused by ectopic pregnancy [75][76][77][78][79][80]. Because the transcriptome data show that TLR3-deficiency causes dysregulation in the gene expression levels of most of the ECM proteins identified by IPA, these data provides insight into a possible mechanism that expounds our recent report demonstrating thatTLR3 deficient mice suffer more severe genital tract pathology than wild-type mice during Cm infection [59].…”
Section: Discussionsupporting
confidence: 85%
“…In the literature the proteolytic cleavage of E-cad was reported for a number of sheddases, including zinc-dependent matrix metalloproteinases (MMP-2, -3, -7, -9 and -14), members of the disintegrin family (adamalysin/ADAM-10 and−15), bacterial proteases gingipains (HRgpA, RgpB, and Kgp), B. fragilis toxin/fragilysin, cysteine cathepsins (B, L, and S), serine protease Kallikrein-7 (KLK7), plasmin serine protease, aspartic proteinases BACE1 and BACE2, and malaria parasite serine proteinases PfSUB2n, PfROM1, and PfROM 4 (Grabowska and Day, 2012). One possible candidate for E-cad cleavage during C. burnetii infections could be the human MMP-9, since: (i) MMP-9 levels were reported elevated in the sera of patients with endocarditis (Thuny et al, 2012), and patients with acute Q fever (Krajinović et al, 2012); (ii) its production was induced in PBMCs of healthy persons following in vitro exposure to C. burnetii ; (iii) MMP-9 SNP was found more frequently in patients with persistent Q fever (Jansen et al, 2017); and (iv) MMP-9 was recently identified as a key gene in mantle cell lymphoma (Yan et al, 2018). Experiments are under progress in our laboratory to investigate whether C. burnetii infection induces the activation of a human cellular protease from the sheddase family or if C. burnetii itself encodes for a sheddase.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix metalloproteinases (MMP) family, count among the inducible human sheddases that catalyze the proteolysis of cadherins (cad), a group of cell-surface adhesion molecules that includes E-cadherin (E-cad) and belongs to the superfamily of CAM (Grabowska and Day, 2012). Recently, we reported (Jansen et al, 2017) that C. burnetii induces the sheddases MMP-1 and MMP-9 production in PBMCs of healthy persons exposed in vitro to the bacterium; that the single nucleotide polymorphisms (SNPs) in MMP-7 and MMP-9 were more frequent in patients with persistent Q fever; and, that the circulating MMP-7 serum levels were higher in patients with persistent Q fever.…”
Section: Introductionmentioning
confidence: 99%